Determinants of High School Student Knowledge on HIV/AIDS - Lidia Sari, Nirma (Basic and Applied Nursing Research Journal, 2023)
Introduction: The number of people living with HIV/AIDS in Indonesia has increased. Because adolescents are the age group that experiences the most rapid social change, they are among the most likely to be infected with HIV or AIDS. This study aimed to determine the determinants of knowledge of SMA 6 Bandar Lampung students about HIV/AIDS. Methods: An observational study with a cross-sectional design is the approach that this research method takes. Students enrolled in the 12th grade at SMA Negeri 6 Bandar Lampung made up both the population and the sample for this study. Results: According to the findings of this study, the majority of students are female (62.7 %), with the majority also being over the age of 17 (97.1 %), and 89.2 % being Muslim. Only 24.5 % of respondents get their health information from health workers, despite the fact that 81.4 % of students are aware of HIV/AIDS. Gender and previous lead exposure are both factors that affect a student's level of knowledge. Conclusion: Schools need to increase the amount of information about HIV/AIDS that students are exposed to in a variety of different ways in order to increase students' knowledge about HIV/AIDS. These ways include incorporating material about adolescent reproductive health into the school curriculum, creating peer study groups, and increasing education and information through the media.